Antibacterial Activity of V2O5 Nanoparticles - Subramanian, P.; David, S. Alwin (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The chemical synthesis of vanadium pentoxide nanoparticles (V2O5 NPs) is presented in this article. The formation of V2O5 NPs is confirmed by the 508 cm-1 band visible in the Fourier-transform infrared spectrum. According to the scanning electron microscopy analysis, the 40–50 nm-sized V2O5 NPs resemble sponges. The size of V2O5 NPs is in between 33.72 and 52.78 nm, as shown by XRD. The antibacterial capabilities of V2O5 NPs were evaluated against Staphylococcus aureus and Bacillus cereus. Moderate antibacterial activity is exhibited by the synthesized V2O5 NPs.